An Economical and Flexible Dual Barcoding, Two-Step PCR Approach for Highly Multiplexed Amplicon Sequencing - Pjevac, Petra; Hausmann, Bela; Schwarz, Jasmin; Kohl, Gudrun; Herbold, Craig W.; Loy, Alexander; Berry, David (Frontiers in Microbiology, 2021)
In microbiome research, phylogenetic and functional marker gene amplicon sequencing is the most commonly-used community profiling approach. Consequently, a plethora of protocols for the preparation and multiplexing of samples for amplicon sequencing have been developed. Here, we present two economical high-throughput gene amplification and sequencing workflows that are implemented as standard operating procedures at the Joint Microbiome Facility of the Medical University of Vienna and the University of Vienna. These workflows are based on a previously-published two-step PCR approach, but have been updated to either increase the accuracy of results, or alternatively to achieve orders of magnitude higher numbers of samples to be multiplexed in a single sequencing run. The high-accuracy workflow relies on unique dual sample barcoding. It allows the same level of sample multiplexing as the previously-published two-step PCR approach, but effectively eliminates residual read missasignments between samples (crosstalk) which are inherent to single barcoding approaches. The high-multiplexing workflow is based on combinatorial dual sample barcoding, which theoretically allows for multiplexing up to 299,756 amplicon libraries of the same target gene in a single massively-parallelized amplicon sequencing run. Both workflows presented here are highly economical, easy to implement, and can, without significant modifications or cost, be applied to any target gene of interest.